2007
DOI: 10.1354/vp.44-5-621
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Circovirus Type 2-Associated Cerebellar Vasculitis in Postweaning Multisystemic Wasting Syndrome (PMWS)-Affected Pigs

Abstract: Porcine circovirus type 2 (PCV2) is associated with several syndromes in growing pigs, including postweaning multisystemic wasting syndrome and porcine dermatitis and nephropathy syndrome. In the present study, a previously undescribed neurovascular disorder associated with a PCV2 infection is described. Sixteen pigs showed clinical signs of wasting and neurologic deficits. Acute hemorrhages and edema of cerebellar meninges and parenchyma due to a necrotizing vasculitis resulted in degeneration and necrosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
3
51
1
Order By: Relevance
“…4,13,22,23 PCV2 antigen was detected in endothelial cells, smooth muscle cells of the tunica media, infiltrating leukocytes, intravascular and perivascular macrophages, and intravascular monocytes in the present study and in previous reports. 4,11,[13][14][15]17,[21][22][23] Furthermore, intimal spindle cell proliferation was found in a few cases (data not shown) and was recently reported in a cesarean-derived/colostrum-deprived pig inoculated with PCV2b. 13 No correlation was found between the number of infected cells and the presence or severity of the vascular lesions, suggesting a host immune system-induced alteration rather than a direct PCV2-induced lesion.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…4,13,22,23 PCV2 antigen was detected in endothelial cells, smooth muscle cells of the tunica media, infiltrating leukocytes, intravascular and perivascular macrophages, and intravascular monocytes in the present study and in previous reports. 4,11,[13][14][15]17,[21][22][23] Furthermore, intimal spindle cell proliferation was found in a few cases (data not shown) and was recently reported in a cesarean-derived/colostrum-deprived pig inoculated with PCV2b. 13 No correlation was found between the number of infected cells and the presence or severity of the vascular lesions, suggesting a host immune system-induced alteration rather than a direct PCV2-induced lesion.…”
Section: Discussionsupporting
confidence: 84%
“…18 Involvement of the vasculature in PCV2 infection has been reported. 2,4,13,17,22,23 In vitro endothelial activation and diminished coagulation time in swine naturally infected with PCV2 were demonstrated. These changes and the presence of PCV2 antigen in endothelial cells of naturally infected pigs pointed to PCV2 infection as the cause of vascular lesions.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Studies conducted by several research groups have identified apoptosis by TUNEL assay (Shibahara et al, 2000;Krakowka et al, 2004;Mandrioli et al, 2004;Resendes et al, 2004a;Seeliger et al, 2007) and CCasp3 IHC (Resendes et al, 2004a,b;Seeliger et al, 2007) in conventional, clinically-affected pigs (Rosell et al, 1999(Rosell et al, , 2000b. A recent investigation on conventional pigs using the TUNEL assay, CCasp3 IHC and PCV2 in situ hybridization (ISH) provided evidence of virus-induced apoptosis in endothelial cells in pigs diagnosed with PCV2-associated cerebellar vasculitis (Seeliger et al, 2007). Similarly, a study using conventional clinically-affected pigs, the TUNEL assay and PCV2 ISH found that diminished lymphoid cell proliferation was the actual cause of cell depletion (Mandrioli et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, microscopic lesions were found only in the lungs, where multinucleated giant cells and prominent vascular lesions were detected first, with the parallel presence of nonsuppurative pneumonia. The presence of multinucleated giant cells in pig fetuses has so far been described only in the lymphoid organs (Opriessnig and Langohr, 2012) and vascular lesions have been reported only in growing and adult pigs with PMWS or PRDC (Opriessnig et al, 2006;Correa et al, 2007;Seeliger et al, 2007;Langohr et al, 2010;Szeredi et al, 2012;Resendes and Segalés, 2014). The presence of large amounts of PCV2 antigen in and around the blood vessels of different fetal organs suggests that the vascular system may be important in the pathogenesis of fetal PCV2 infection as well.…”
Section: Discussionmentioning
confidence: 99%